History repeating. The plague of 1630 in Milan and the COVID-19 pandemia - Ciulla, Michele M (Acta Biomedica Atenei Parmensis, 2020)
In western democracies, individual behaviour will be crucial to control the spread of COVID-19, as well as government actions [1] that unfortunately, except China, South Korea and Italy, followed by others,  seems to be generally unconvinced and, speculatively, late. Indeed human history has been marked by epidemics/pandemics which have affected, more or less, large geographical areas [2]. Italy, as well as the rest of Europe, has often been affected by these phenomena and, Lombardy, due to his position, was, as today by COVID-19, severely stroked in Italy that is, after China, the second most affected country [3]. This is also linked to the position of Lombardy and its capital, Milan, but this is beyond this brief comment. There are several differences between the past plagues and the actual COVID-19 pandemic and these must be sought in the increased ability to transmit diseases at-distance through the mobility of humans and goods [4], and in the catastrophic consequences of the breakdown of ecosystems, as told, a few years ago, by David Quammen in the book Spillover [5].